2017
DOI: 10.17148/ijireeice.2017.5308
|View full text |Cite
|
Sign up to set email alerts
|

A Study on System Reliability in Weibull Distribution

Abstract: This paper presented the estimation of system reliability using two parameter Weibull distribution. The parameters are estimated using Weibull probability plot & statistical analysis and the results being presented in charts. An increasing complexity of systems often leads to an increase of failure mechanisms. A statistical analysis of the lifetime of systems with several failure mechanisms consisting of several subcomponents considered The Weibull distribution is commonly used as a lifetime distribution in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…The Weibull model is one among the few essential distributions used in reliability theory that are crucial to understanding dependability applications. Many of the analyses using the Weibull model are now available across the engineering literature [18,22,27]. Fisher and Tippett [31] proposed a basic theory of the Weibull distribution as one of three types of extreme value distributions.…”
Section: Introductionmentioning
confidence: 99%
“…The Weibull model is one among the few essential distributions used in reliability theory that are crucial to understanding dependability applications. Many of the analyses using the Weibull model are now available across the engineering literature [18,22,27]. Fisher and Tippett [31] proposed a basic theory of the Weibull distribution as one of three types of extreme value distributions.…”
Section: Introductionmentioning
confidence: 99%
“…Gorjian Jolfaei et al evaluated the reliability of the power generation system in order to minimize the operating and maintenance costs in waste-water treatment plants with the two-parameter Weibull model [11]. Kumar and Krishnan estimated the reliability evaluation and the expected first failure time with two-parameter Weibull Distribution using the MTBF criteria of twenty-four diesel compressors of the same brand and model [12]. Li et al determined the lower and upper limits of reliability of electrical elements with three-parameter generalized inverse Weibull [13].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the two‐parameter Weibull model was found to be useful for the performance analysis of redundant systems and can provide maintenance strategies when the random variable follows the Weibull distribution . In reported case studies, the two‐parameter Weibull model was applied for reliability assessment of electromagnetic valves in a high‐speed electric unit, diesel engines, and jaw crushers …”
Section: Introductionmentioning
confidence: 99%
“…29 In reported case studies, the two-parameter Weibull model was applied for reliability assessment of electromagnetic valves in a high-speed electric unit, diesel engines, and jaw crushers. [30][31][32] No studies reporting system reliability modelling of power generation in WWTPs were found in the literature. This case study aims to develop power generation system reliability and availability modelling considering redundancy to minimise operation and maintenance costs.…”
Section: Introductionmentioning
confidence: 99%